Shifts in Modern Commitment: The Phenomenon of Fear of Marriage and Childfree from an Evolutionary Psychology Perspective - Nabila Atika Ajra; Mela Desina; Yuliana Intan Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomena of fear of marriage (gamophobia) and the choice to live a childfree life have become increasingly prominent among younger generations, reflecting a shift in values regarding commitment, marriage, and reproduction. This article aims to analyze these phenomena through the perspective of evolutionary psychology. Using a qualitative literature review approach, this study examines scholarly books and journal articles related to gamophobia, childfree lifestyles, life history theory, and evolutionary mismatch. The findings indicate that fear of marriage can be understood as an adaptive response to the high evolutionary costs of long-term commitment, including perceived threats to autonomy, relational instability, and economic uncertainty. Meanwhile, the decision to remain childfree represents an alternative reproductive strategy when environmental conditions are perceived as unfavorable for parental investment. These results suggest that contemporary attitudes toward marriage and reproduction are not merely a rejection of traditional norms but reflect adaptive psychological strategies in response to modern social and ecological pressures.